The path of decentralization in the second republic of Tunisia after 2011 (قضايا سياسية, 2024)
Decentralization, in both its administrative and political forms, is linked to a specific political philosophy that establishes democratic rule and thus meets the needs of the members of society, as it is based on a set of requirements that almost amount to scientific laws. “The success of administrative and political decentralization” does not only include slogans, but also on the projects involved. For all the political, legal, and even psychological dimensions, one of the important and pivotal conditions is not to weaken the center, or fragment the authorities in the state and weaken the pillars and foundations of the democratic center. Therefore, the adoption of administrative and political decentralization should be within a gradual framework and within the context of benefiting from previous Tunisian experiences. And the experiences of other countries, as there must be political, democratic and professional elites capable of achieving the necessary harmony between the slogan and the project in the approach of the Tunisian ruling regime after 2011, based on the aspirations of the ruling regime in Tunisia according to the 2014 Constitution, and it constitutes a method of regimes. The ruling political system, according to which each region and entity has the right to manage and facilitate its local affairs in a natural way, and it is considered as an attribution of legal personality to independent entities within the state that represent human groups in a specific territorial area, that take their decisions independently through an elected body, and this was due to the weakness of the regional-municipal performance and the lack of The existence of the official development alternative, which the country suffered from as a result of the lack of state resources and their limitations, is a major challenge to the path of decentralization in the country’s second republic. Decentralization was recognized in order to achieve development in regions and regions that complain of marginalization, and to emphasize rights and freedoms according to the country’s constitution in 2014.